Antifungal and Antibiofilm Efficacy of Paeonol Treatment Against Biofilms Comprising Candida albicans and/or Cryptococcus neoformans - Qian, Weidong; Li, Xinchen; Liu, Qiming; Lu, Jiaxing; Wang, Ting; Zhang, Qian (Frontiers in Cellular and Infection Microbiology, 2022)
Fungal populations are commonly found in natural environments and present enormous health care challenges, due to increased resistance to antifungal agents. Paeonol exhibits antifungal activities; nevertheless, the antifungal and antibiofilm activities of paeonol against Candida albicans and Cryptococcus neoformans remain largely unexplored. Here, we aimed to evaluate the antifungal and antibiofilm activities of paeonol against C. albicans and/or C. neoformans (i.e., against mono- or dual-species). The minimum inhibitory concentrations (MICs) of paeonol for mono-species comprising C. albicans or C. neoformans were 250 μg ml−1, whereas the MIC values of paeonol for dual-species were 500 μg ml−1. Paeonol disrupted cell membrane integrity and increased the influx of gatifloxacin into cells of mono- and dual-species cells, indicating an antifungal mode of action. Moreover, paeonol at 8 times the MIC damaged mono- and dual-species cells within C. albicans and C. neoformans biofilms, as it did planktonic cells. In particular, at 4 and 8 mg ml−1, paeonol efficiently dispersed preformed 48-h biofilms formed by mono- and dual-species cells, respectively. Paeonol inhibited effectively the yeast-to-hyphal-form transition of C. albicans and impaired capsule and melanin production of C. neoformans. The addition of 10 MIC paeonol to the medium did not shorten the lifespan of C. elegans, and 2 MIC paeonol could effectively protect the growth of C. albicans and C. neoformans-infected C. elegans. Furthermore, RNA sequencing was employed to examine the transcript profiling of C. albicans and C. neoformans biofilm cells in response to 1/2 MIC paeonol. RNA sequencing data revealed that paeonol treatment impaired biofilm formation of C. albicans by presumably downregulating the expression level of initial filamentation, adhesion, and growth-related genes, as well as biofilm biosynthesis genes, whereas paeonol inhibited biofilm formation of C. neoformans by presumably upregulating the expression level of ergosterol biosynthesis-related genes. Together, the findings of this study indicate that paeonol can be explored as a candidate antifungal agent for combating serious single and mixed infections caused by C. albicans and C. neoformans.